Impact of Climate Change: Understanding the Impact of Climate Change on Global Health (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Various risks posed by climate change are significant, distributed throughout the world and hard to reverse. Climate changes threatens the essential component of health, drinking water, fresh air and nutritious food items and has the capability to destroy decades of progress achieved in global health. It also poses new challenges to the control of various infectious diseases and gradually increasing the pressure on the natural, social and economic systems that support and sustain health. Climate change continuously increasing the frequency and intensity of heat waves, droughts, flood and cyclones in various part of the globe and altering the transmission of air-borne, water-borne and vector-born infectious diseases, resulting in negative impacts on human health. People living on small islands, low-lying areas and those in the under developed countries are most affected and at higher risk.Earth's temperature has increased by 1.20C and if the rate of carbon emission remains the same, then anytime between 2030 and 2050, the temperature is expected to increase by 1.50C. Between 2030 and 2050, climate change is expected to cause numerous additional deaths per year, from malnutrition, malaria, diarrhoea and heat stroke alone. Scientists clearly believe that if the temperature of the earth gets above 20C, then a severe form of climate change will be seen and the weather changes will be at the peak. Such conditions and other health outcomes will be increasingly affected by accelerating climate change through its adverse effects on food production, water availability and the population and transmission cycle of various vectors and pathogens.